Audience loyalty as the main prerequisite for trade press thriving - Varenyk, Valentyna M.; Trishchuk, Olga V. (Linguistics and Culture Review, 2021)
Modern publishing businesses need a complex roadmap for developing print and digital directions, and lack of the strategy for media means overload with unnecessary current activities for employees, lack of attention to readers and advertisers and dissatisfaction with the financial achievements by head office. The proposed paper attempts to understand the usage patterns and preferences of audience for print trade magazine. The questionnaire is based on the theory of the functions of the trade press to make sure that the magazine performs the established functions for its audience. The data also helped establish the demographics of the magazine's audience. The findings of the study enable to throw light on the present media usage habits and to examine the trade media consumption behavior. The study showed that the audience of the trade media is very homogeneous and characterized by similar socio-economic characteristics. Even though the study gives insights into current trade press preferences of audience, the results may not be generalized as every audience has own territorial, gender and financial differences and diversified socio-economic background. The study can be further extended by taking a sample from different types of trade media.